Sectioning on the street – futility or utility?. (December 2016) - Timms, Philip; Perry, Jennifer
Abstract : Aims and method: A service evaluation was undertaken to examine outcomes in patients who were street homeless ('rough sleepers') and who were compulsorily admitted to hospital under the Mental Health Act 1983. The data were collected from the patients' case notes. Results: At 1-year follow-up, patients had positive outcomes in areas such as accommodation status, registration with a general practitioner and engagement with the clinical team. Clinical implications: The study shows that the intervention of a Mental Health Act assessment and compulsory hospital admission in homeless people on the street is associated with positive outcomes at 1 year.